Working Conditions as a Predictor of Employees’ Well-Being in Selected Broadcasting Organisations in Southwestern Nigeria - Ogunola, Abiodun Adekunle (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
The study examined the predictability of working conditions on the well-being of employees of selected broadcasting organisations in Southwestern Nigeria. It also assessed the differences in the well-being of these employees based on their form of ownership. A research questionnaire comprising of standardized instruments: the Copenhagen Psychosocial Questionnaire and the Work and Well-being Outcome Scale were used to generate data from the respondents. A sample of 412 employees in the eleven selected broadcasting organisations participated in the study. This study made use of both descriptive and inferential statistics such as frequencies, means, multiple regression, least squared difference, and Analysis of Variance (ANOVA) to analyse data. The results indicated that working conditions which is a compendium of various organizational factors within the selected broadcasting organizations significantly predicted employees’ well-being of the selected organizations. Differences were also found in the well-being of employees of federal, state, and privately-owned broadcasting organisations as these employees are exposed to different physical and psychosocial work environments based on the level of structure and organization of tasks, activities, and the physical and human resources available to these organizations. The study concluded that having pleasant working conditions can play a crucial role in the retention of satisfied and loyal employees and the promotion of their all-round well-being.